Race-Based Real Estate Practices and Spuriousness in Community Criminology: Was the Chicago School Part of a Self-Fulfilling Prophecy? - Linning, Shannon J. (Criminal justice review, 2025)
For over a century, a small network of scholars, extending from the University of Chicago, shaped community criminology research. Drawing on human ecology, they argued that poor structural factors—poverty, ethnic heterogeneity, population mobility—cause crime. As this network studied crime in neighborhoods, another network changed neighborhoods. This other network also assumed structural factors were important, but its members developed policies and practices to alter them. This other network, also influenced by human ecology, was composed of real estate researchers. Historical records show that the two networks are connected. These connections raise the possibility of a self-fulfilling prophecy. The implications of the prophecy are that the correlations between structural factors and crime may be spurious. We show that real estate practices shaped structural factors. But the structural factors may not drive crime. Instead, real estate practices may have shaped crime opportunities through place management thus driving crime. This has serious implications for community criminology research. This theoretical paper lays out the historical evidence for this conjecture.